The impact of DNA tumor viruses in low-to-middle income countries (LMICS): A literature review - Bothwell Takaingofa Guzha; Allen Matubu; George Nyandoro; Hamish O. Mubata; Enos Moyo; Grant Murewanhema; Zvavahera M. Chirenje (Tumour Virus Research)
DNA viruses are common in the human population and act as aetiological agents of cancer on a large scale globally. They include the human papillomaviruses (HPV), Epstein-Barr virus (EBV), Kaposi sarcoma-associated herpesvirus (KSHV), hepatitis viruses, and human polyomaviruses. Oncogenic viruses employ different mechanisms to induce cancer. Notably, cancer only develops in a minority of individuals who are infected, usually following protracted years of chronic infection. The human papillomaviruses (HPVs) are associated with the highest number of cancer cases, including cervical cancer and other epithelial malignancies. Hepatitis B virus (HBV) and the RNA virus hepatitis C (HCV) are significant contributors to hepatocellular cancer (HCC). Other oncoviruses include Epstein-Barr virus (EBV), Kaposi sarcoma-associated herpes virus (KSHV), human T-cell leukemia virus (HTLV-I), and Merkel cell polyomavirus (MCPyV). The identification of these infectious agents as aetiological agents for cancer has led to reductions in cancer incidence through preventive interventions such as HBV and HPV vaccination, HPV-DNA based cervical cancer screening, antiviral treatments for chronic HBV and HCV infections, and screening of blood for transfusion for HBV and HCV. Successful efforts to identify additional oncogenic viruses in human cancer may provide further understanding of the aetiology and development of cancer, and novel approaches for prevention and treatment. Cervical cancer, caused by HPV, is the leading gynaecological malignancy in LMICs, with high age-standardised incidence and mortality rates, HCC due to HBV is an important cause of cancer deaths, and the burden of other cancer attributable to infections continues to rise globally. Hence, cancers attributable to DNA viruses have become a significant global health challenge. These viruses hence warrant continued attention and interrogation as efforts to understand them further and device further preventive interventions are critical.